Simultaneous analysis of mirtazapine and N-demethylmirtazapine in plasma by high-performance liquid chromatography (Revista Brasileira de Ciências Farmacêuticas, 2005)
Simple, sensitive and selective analytical methods are required for pharmacokinetic studies and therapeutic drug monitoring of mirtazapine, a new antidepressant drug. Thus high-performance liquid chromatography with fluorescence detection was used for the simultaneous analysis of mirtazapine and its metabolite, N-demethylmirtazapine, in plasma. After liquid-liquid extraction with toluene, the drug, metabolite and internal standard (metoprolol) were resolved using a LiChrospher 100 RP-8 endcapped column with a mobile phase of 0.1 mol/L phosphate buffer, pH 3.5-acetonitrile (82:18, v/v). The method was linear in the range of 2.5 to 500 ng/mL for both analytes, with mean recoveries of 77% and 66% for mirtazapine and N-demethylmirtazapine, respectively. The quantification limits (2.5 ng/mL), precision (CV < 15%) and accuracy (relative errors < 15%) indicate the method is suitable for pharmacokinetic studies and therapeutic drug monitoring.